Antidepressant-like effects of electroconvulsive seizures require adult neurogenesis in a neuroendocrine model of depression - Schloesser, Robert J. (Brain Stimul, 2015)
BACKGROUND: Neurogenesis continues throughout life in the hippocampal dentate gyrus. Chronic treatment with monoaminergic antidepressant drugs stimulates hippocampal neurogenesis, and new neurons are required for some antidepressant-like behaviors. Electroconvulsive seizures (ECS), a laboratory model of electroconvulsive therapy (ECT), robustly stimulate hippocampal neurogenesis. HYPOTHESIS: ECS requires newborn neurons to improve behavioral deficits in a mouse neuroendocrine model of depression. METHODS: We utilized immunohistochemistry for doublecortin (DCX), a marker of migrating neuroblasts, to assess the impact of Sham or ECS treatments (1 treatment per day, 7 treatments over 15 days) on hippocampal neurogenesis in animals receiving 6 weeks of either vehicle or chronic corticosterone (CORT) treatment in the drinking water. We conducted tests of anxiety- and depressive-like behavior to investigate the ability of ECS to reverse CORT-induced behavioral deficits. We also determined whether adult neurons are required for the effects of ECS. For these studies we utilized a pharmacogenetic model (hGFAPtk) to conditionally ablate adult born neurons. We then evaluated behavioral indices of depression after Sham or ECS treatments in CORT-treated wild-type animals and CORT-treated animals lacking neurogenesis. RESULTS: ECS is able to rescue CORT-induced behavioral deficits in indices of anxiety- and depressive-like behavior. ECS increases both the number and dendritic complexity of adult-born migrating neuroblasts. The ability of ECS to promote antidepressant-like behavior is blocked in mice lacking adult neurogenesis. CONCLUSION: ECS ameliorates a number of anxiety- and depressive-like behaviors caused by chronic exposure to CORT. ECS requires intact hippocampal neurogenesis for its efficacy in these behavioral indices.